Batik Artisans’ judgment of batik wax quality and its criteria: an application of the Many-facet Rasch Model - Kudiya, K.; Sumintono, B.; Sabana, S.; Sachari, A. (2016)
Batik is a traditional dyeing technique that uses hot melted wax on natural fabric. The wax is applied to fabric, left to dry then dyed using cold water dyes. Wax quality is central to the batik process and there are ten standard criteria used to measure the batik wax quality. This study used five batik wax samples tested by twenty batik artisans according to the standard criteria. The data analyzed using the many-facet Rasch Model. The study found that certain criterion like the cost of wax making is sensitive for the batik artisans. Two criteria of batik wax quality, namely ‘easy to freeze’ and ‘not sticky’ are two items that make the judgments’ result that created unexpected responses from raters.